Dysregulated expression of microRNAs and mRNAs in myocardial infarction - Wang, Yaping (Am J Transl Res, 2015)
Acute myocardial infarction (AMI) is a major cause of mortality in the general population. However, the molecular phenotypes and therapeutic targets of AMI patients remain unclear. By profiling genome-wide transcripts and microRNAs (miRNAs) in a cohort of 23 AMI patients and 23 non-AMI patients, we found 218 dysregulated genes identified in the infarcted heart tissues from AMI patients relative to non-AMI controls. Pathway enrichment analysis of the dysregulated genes pointed to cell signaling/communication, cell/organism defense and cell structure/motility. We next compared the expression profiles of potential regulating miRNAs, suggesting that dysregulation of a number of AMI-associated genes (e.g., IL12A, KIF1A, HIF1α and CDK13) may be attributed to the dysregulation of their respective regulating miRNAs. One potentially pathogenic miRNA-mRNA pair, miR-210-HIF1α, was confirmed in a mouse model of myocardial infarction (MI). Inhibition of miR-210 expression improved the survival and cardiac function of MI mice. In conclusion, we presented the pathologic relationships between miRNAs and their gene targets in AMI. Such deregulated microRNAs and mRNAs like miR-210 serve as novel therapeutic targets of AMI.